2012
DOI: 10.1097/qad.0b013e3283558459
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV and chronic comorbidities among older adults

Abstract: Objectives Limited evidence is available on HIV, aging and comorbidities in sub-Saharan Africa. This article describes the prevalence of HIV and chronic comorbidities among those aged 50 years and older in South Africa using nationally representative data. Design The WHO’s Study of global AGEing and adult health (SAGE) was conducted in South Africa in 2007–2008. SAGE includes nationally representative cohorts of persons aged 50 years and older, with comparison samples of those aged 18–49 years, which aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
105
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 32 publications
7
105
1
Order By: Relevance
“…[7] Notably, there is work that suggests that 30% of older patients with HIV may have comorbidity with other chronic diseases. [16] It is also possible that treatment for NCDs is being given to HIV-positive patients in HIV clinics. Future research is required to investigate these comorbid conditions within the HIV context, especially as HIV-positive patients who were diagnosed in young adulthood mature.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Notably, there is work that suggests that 30% of older patients with HIV may have comorbidity with other chronic diseases. [16] It is also possible that treatment for NCDs is being given to HIV-positive patients in HIV clinics. Future research is required to investigate these comorbid conditions within the HIV context, especially as HIV-positive patients who were diagnosed in young adulthood mature.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on health expenditure and catastrophic spending conducted on adult populations cannot necessarily be extrapolated to older people who differ in terms of poverty rates (Ramashala, 2001), health access, and disease burden (Albanese et al, 2011;Negin, Martiniuk, et al, 2012).…”
mentioning
confidence: 99%
“…An estimated 4.2 million people worldwide aged 50 and older are living with HIV (Mahy, Autenrieth, Stanecki, & Wynd, 2014), with recent estimates from South Africa predicting HIV prevalence in adults aged 50 and older will nearly double from 9% in 2010 to 17% in 2040. Older adults with HIV face a greater health and financial burden, with greater risk of non-communicable diseases (Negin, Barnighausen, Lundgren, & Mills, 2012;Negin, Martiniuk, et al, 2012).…”
mentioning
confidence: 99%
“…Sub-Saharan Africa is lagging behind in terms of literature on the characteristics of HIV infection in older adults. Negin et al found that 29.6% of persons aged 50 years and above in South Africa had two or more chronic diseases compared to 8.8% in age group 18-49 years 15 . Meanwhile, Nyirenda et al showed that older adults in Uganda and South Africa had poorer emotional and functional wellbeing 16 .…”
mentioning
confidence: 99%